Pengaruh Disiplin Kerja dan Motivasi Kerja Terhadap Kinerja Karyawan Pada PT Timah Tbk Perwakilan Jakarta di Jakarta Pusat - Nur Halipah; Bachtiar Arifudin Husein (Manajemen Kreatif Jurnal, 2024)
The aim of this research is to determine the influence of work discipline and work motivation on employee performance at PT Timah Tbk Jakarta Representative in Central Jakarta, both partially and simultaneously. The method used is a quantitative method. Data analysis uses data instrument tests, classical assumption tests, descriptive analysis, quantitative analysis and hypothesis testing. The results of this research are that work discipline has a significant effect on employee performance with the regression equation Y = 7.584 + 0.784X1. The correlation coefficient value is 0.789, meaning it has a very strong relationship. The coefficient of determination value is 0.622 or 62.2% while the remaining 37.8% is influenced by other factors. Hypothesis testing obtained t count > t table (8.884 > 1.677). Thus, H0 is rejected and H1 is accepted, meaning that there is a partially significant influence between work discipline on employee performance at PT Timah Tbk Jakarta Representative in Central Jakarta. Work Motivation has a significant effect on Employee Performance with the regression equation Y = 4.393 + 0.872X2. The correlation coefficient value is 0.917, meaning it has a strong relationship with employee performance. The coefficient of determination value is 0.841 or 84.1% while the remaining 15.9% is influenced by other factors. Hypothesis testing obtained t value > t table (15.914 > 1.677). Thus, H0 is rejected and H2 is accepted, meaning that there is a partially significant influence between work motivation and employee performance at PT Timah Tbk, Jakarta Representative in Central Jakarta. Work Discipline and Work Motivation have a significant effect on employee performance with the regression equation Y = 3.721 + 0.079X1 + 0.809X2. The correlation coefficient value is 0.918, meaning it has a very strong relationship. The coefficient of determination value is 0.843 or 84.3% while the remaining 15.7% is influenced by other factors. Hypothesis testing obtained calculated F value > F table (125.792 > 2.802). Thus, H0 is rejected and H3 is accepted, meaning that there is a significant simultaneous influence between Work Discipline and Work Motivation on Employee Performance at PT Timah Tbk Jakarta Representative in Central Jakarta.